Figure it out!: permainan bahasa kreatif dalam pembelajaran bahasa Inggeris sebagai bahasa kedua (Figure it out!: a language game to promote creative use of expressions in ESL writing classrooms) / Nalini Arumugam … [et al.] - Arumugam, Nalini; Mohd Noor, Maizura; Bala Subramaniam, Asha Latha; Munchar, Julina; Selvanayagam, Sivajothy; Md Supie, Hawa Syamsina; Lin, Nur Maizura; Syed Nasharudin, Sharifah Nadia (Universiti Teknologi MARA, 2020)
This study aims to enhance students’ writing task of the Malaysian University English Test (MUET) by utilising figurative devices, especially similes, metaphors, idioms, hyperboles and proverbs. This study adopted a mixed-method design; pretest, post-test; structured interview and learners’ perceptions on using a board game in the ESL writing class. This study involved two phases. In Phase One, the students went through a pretest. Then, they played FIGURE IT OUT four times before sitting for the posttest. The students showed a marginal improvement; pretest =11.5172 (m) and post-test =12.3966 (m). The learners, in the structured interview, expressed joy playing the game, although it was slightly challenging as some of them lacked exposure in figurative expressions. Then the board game was revised. In Phase Two, the game included three different levels of figurative expressions. The learners had the opportunity to play according to their levels. Once they completed Level 1 of the game with at least 75% of correct answers, they were allowed to proceed to Levels Two and Three. In Phase 2, there was control and experimental groups. Both groups sat for the pre and post-tests. The learners in the control group learned writing skill through the common communicative way by working individually and in small groups. As for the experimental group, the leaners played FIGURE IT OUT six times. The results indicated that both groups showed improvement; the control group scored an average mean M=16.1471 in the pretest and scored M=17.8095 in the post-test while the experimental group showed a significant improvement with (M=16.1471) pretest to post-test (M=18.5294), p+.000. The learners shared that the game provided them with the opportunity to explore and exploit figurative expressions. They revealed that they had fun playing the game and learned to use the symbolic terms not only in their writing tasks but also in their daily communication.